Historical Analysis of Sea Ice Conditions in M'Clintock Channel and the Gulf of Boothia, Nunavut : Implications for Ringed Seal and Polar Bear Habitat - Barber, D.G.; Iacozza, J. (ARCTIC, 2004)
Sea ice is an integral part of the marine ecosystem in the Arctic and important habitat for ringed seals and polar bears. To study changes in sea ice characteristics indicative of ringed seal habitat (and linked, through predator/prey relationships, to polar bear habitat), we examined historical changes in sea ice concentration and type within M'Clintock Channel and the Gulf of Boothia, two regions of the Canadian Arctic Archipelago, during 1980-2000. Results suggest large interannual variability in winter ice conditions over the 21-year study period. In M'Clintock Channel, first-year ice types dominated consistently, while in the Gulf of Boothia, thick ice types dominated in some years. For breakup and consolidation, the regional spatial patterns differed significantly, occurring in opposite directions (N-S vs. S-N) in the two regions. The dates showed considerable interannual variability in both regions, suggesting no clear pattern of either earlier breakup or later consolidation. Analysis of satellite data confirmed the results obtained from digital ice charts. Ringed seal habitat suitability indices (HSI) indicate that both regions contained primary, secondary, and tertiary HSI classes. No trends were evident in the secondary or tertiary classes, but changes in the primary class were evident in M'Clintock Channel over the five-year period 1997-2001. Dynamic and thermodynamic sea ice processes are important to ringed seal habitat (and ultimately, polar bear habitat) at regional and hemispheric scales in the current context of climate variability and change. La glace de mer fait partie intégrante de l'écosystème marin de l'Arctique et constitue un important habitat pour le phoque annelé et l'ours polaire. Au cours des années comprises entre 1980 et 2000, afin d'étudier les changements dans les caractéristiques de glace marine dénotant un habitat de phoque annelé (et donc associé à un habitat d'ours polaire par l'intermédiaire de la relation prédateur / proie), on a examiné des changements historiques dans la ...